Platelet-rich Plasma Versus Steroid Injection under C-Arm Guidance in the Management of Sacroiliitis - Ashutosh Kumar; Rishabh Kumar; Anand Shankar; Rakesh Kumar (Journal of Orthopaedic Diseases and Traumatology, 2024)
OBJECTIVE: The objective is to evaluate the efficacy of platelet-rich plasma and steroid injection in the management of sacroiliitis. Background: Sacroiliitis is considered a diagnostic feature of seronegative spondyloarthropathy (SPA). Sacroiliac joint steroid injection is the most commonly used method. Currently steroid, injection therapy and platelet-rich plasma (PRP) therapy are current treatment trends. Material and Methods: This interventional study included 60 patients with seronegative axial SPA. Patients were divided into two groups: group I received a c arm guided steroid injection and group II received a PRP injection. Patients were assessed by Visual Analog Scale and Modified Oswestry Disability Questionnaire (MODQ) at 4 and 8 weeks postinjection and by magnetic resonance imaging (MRI) at 8 weeks postinjection. Result: Steroids and PRP are effective in treating sacroiliitis. The improvement was significant and lasted longer in group II (68.6% mild pain by Vas and 74.3% minimal disability related to MODQ) compared to group I at 8 weeks postinjection. Steroid-treated patients improved significantly in 4 weeks (60% of patients experienced mild pain in Vas and 45.7% had minimal defects in MODQ), but efficacy declined after 8 weeks. According to follow-up MRI, active sacroiliitis can be completely improved with PRP injection (57.1% with normal MRI results after 8 weeks). Conclusion: Steroids and PRP were effective in the treatment of sacroiliitis in seronegative SPA under C arm guidance. But PRP was persistent and prolonged.